How Misleading Can The Analysis of Human Eye Movements Be? Experiments on Dominante Eye and Cognitive Visual Perception - Pinto, Alisson Moriyasu; Romera, João; Thomaz, Carlos (Anais do Workshop de Visão Computacional (WVC), 2024)
Research on the human dominant eye has existed for over 100 years, yet no consistent methodology uses dominant eye data to analyze eye movements in eye-tracking studies. This is concerning, as eye-tracking technology is increasingly important for understanding human visual perception, especially in healthcare decision-making. The aim of this project is to develop an approach for analyzing the dominant eye using Tobii TX300 eye-tracking equipment. The specific objectives are: (1) to create a fast, non-invasive test to determine the dominant eye; (2) to develop a signal acquisition system with various stimuli and pattern recognition; and (3) to analyze results based on dominant eye outcomes. Initial results show divergence between the eyes, but the mean of fixation points from both eyes provides the most accurate mathematical metric with the lowest quadratic errors compared to theoretical fixation points.